(untitled) (African Journal of Biomedical Research, 2022)
Genetic diversity of Plasmodium falciparum is an important feature that makes the parasite a successful pathogen and is a risk factor for generating mutant variants involved in pathogenicity, drug resistance and immune evasion. A study was designed to determine the diversity of P. falciparum isolates based on merozoite surface protein 1 and 2, determine the predominant circulating allelic families and multiplicity of infection in Nigeria. The diagnosis was based on finding the characteristic asexual stage of the parasite in Giemsa-stained blood smears under a compound microscope. The Deoxyribonucleic acid was extracted from P. falciparum positive blood using Chelex extraction method followed by PCR-genotyping, targeting the merozoite surface proteins. Nested polymerase chain reaction and restriction fragment length polymorphisms were used to detect Plasmodium falciparum chloroquine resistance transport, P. falciparum multidrug resistance 1, P. falciparum dihydrofolate reductase and P. falciparum dihydropteroate synthase. Data were analysed using the Statistical Packages for Social Sciences Version 21.0 at a significance level of P<0.05. Overall, multiplicity of infection with MSP 1 and MSP 2 markers was 1.32 and 1.24 respectively. P. falciparum isolates demonstrated diverse nature in respect of MSP 1 (block 2) and MSP 2 (block 3). All the families of MSP 1 and MSP2 were detected. It was concluded that the genetic diversity of P. falciparum was comparatively high. Therefore, strategies that reduce multiple-strain infections should be implemented in order to improve antimalarial drug efficacy and reduce the rate of spread of drug resistance.